The Global, Regional, and National Burden of Psoriasis: Results and Insights From the Global Burden of Disease 2019 Study - Damiani, Giovanni; Bragazzi, Nicola Luigi; Karimkhani Aksut, Chante; Wu, Dongze; Alicandro, Gianfranco; McGonagle, Dennis; Guo, Cui; Dellavalle, Robert; Grada, Ayman; Wong, Priscilla; La Vecchia, Carlo; Tam, Lai-Shan; et al. (Frontiers in Medicine, 2021)
Background: Psoriasis is a common chronic inflammatory , debilitating, systemic disease with great impact on healthcare systems worldwide. As targeted therapies have transformed the therapeutic landscape, updated estimates of psoriasis disease burden are necessary in order to evaluate the impact of past health care policies and orient new national and international health care strategies. Methods: Data were extracted from scientific literature, national surveys, claims data, and primary care sources on the prevalence of psoriasis. Prevalence data were combined with a disability weight to yield years lived with disability(YLDs). Measures of burden at global, regional, and national levels were generated for incidence, prevalence, and YLDs, due to psoriatic disease. All measures are reported as absolute numbers, percentages, and crude and age-adjusted rates per 100,000 persons. In addition, psoriasis burden was assessed by Socio-demographic Index(SDI). Findings: According to the GBD 2019 methodology, worldwide, there were 4,622,594(95% UI 4,458,904 to 4,780,771) incident cases of psoriasis in 2019. The age-standardized incidence rate in 2019 was 57.8(95% UI 55.8 to 59.7)per 100,000 people. With respect to 1990, this corresponded to a decrease by 20.0%(95% UI -20.2 to - 19.8). By sex, the age-standardized incidence rate was similar between males(57.8 (95% UI 55.8 to 59.8)) per 100,000 people and females(57.8(95% UI 55.8 to 59.7))per 100,000 people. With respect to 1990, this corresponded to a decrease by 19.5% (95% UI -19.8 to - 19.2)and by 20.4%(95% UI -20.7 to - 20.2), respectively. The age-standardized incidence rate per 100,000 persons was found to vary widely across geographic locations. Regionally, high-income countries and territories had the highest age-standardized incidence rate of psoriasis(112.6(95% UI 108.9 to 116.1)), followed by high-middle SDI countries(69.4 (95% UI 67.1 to 71.9)),while low SDI countries reported the lowest rate(38.1(95% UI 36.8 to 39.5)).Similar trends were detected for incidence and YLDs. Conclusion: In general, psoriasis burden is greatest in ages 60-69, with relatively similar burden among males and females.The burden is disproportionately greater in high-income and high socio-demographic index countries of North America and Europe. With advances in psoriasis therapeutics, objective evaluation of psoriasis disease burden is critical to track the progress at the population level.